PENGARUH MEDIA SOSIAL TERHADAP INTERAKSI SOSIAL PADA MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI ANGKATAN 2023 - akila, ozza rizwana; Sutja, akmal; ramadhoni, sri rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study uses a quantitative approach with a regression research type. The research sample consisted of 112 students selected using the type of nonprobability sampling technique used in this study is purposive sampling. The considerations or criteria in determining the sample in this study are adjusted to the limitations of the research problem, namely Guidance and Counseling Students of the Class of 2023 who actively use social media platforms such as Instagram, TikTok, and WhatsApp, the research instrument uses a Likert scale that measures the attitudes, opinions, and perceptions of a person or group of people about an educational symptom or phenomenon. The normality test uses a one-sample Kolmogorov Smirnov (K-S) test tool, which is a Goodness of Fit test tool that is carried out by comparing observation scores with a certain theoretical distribution using SPSS statistics. Researchers manage data through the SPSS program, so the criteria for determining whether the curve is normal or not guides the asymptotic significance test (asymp. Sig.) of 0.05. Data is considered normal if it meets the following criteria: a) If the significance value obtained is > 0.05 then the sample comes from a normally distributed population. Based on research results showing that social media has a significant influence on students' social interactions. Keywords: social media, communication problems, students